BIMBINGAN BELAJAR TAHFIDZ SISWA MI MUHAMMADIYAH PK KARTASURA (Peran Orang Tua Sebagai Alat Analisis) - Herri Gunawan (Institut Islam Mamba'ul 'Ulum Surakarta, 2022)
The research aims to find the parents role to Tahfidz learning guidance and its effectiveness at MIMPK Kartasura. The research is a descriptive qualitative research using method triangulation. The main method of data collection was participant observation and interview with informants, either through voice notes and WA. Analysis techniques of data included collecting, analyzing, reducing, presenting, and concluding. The research results were that Tahfidz learning guidance was effective; namely: the openness and some parents desire to actively discuss with teachers regarding the challenges and obstacles faced during the Tahfidz online learning process up to free time from some parents to prepare tools (hardware and software). The research conclusions were that Tahfidz learning during the Covid-19 Pandemic period was online by using talqin/ talaqqi/ tasmi’ method through muraja’ah and setoran; the lack of understanding or attention from parents was the threat to the success of Tahfidz’s learning; preconditions for the learning environment and online Tahfidz learning could not always be presented by some parents and these preconditions caused the role of parents to be less effective; and the decline continuity in students’ internal/ futur conditions could cause students to forget or lose the total memorization of Qur'an.